Examination of the neck when a patient complains of shoulder pain: a global survey of current practice (2019). (12th March 2020) - Walker, Tom; Cuff, Andrew; Salt, Emma; Lynch, Greg; Littlewood, Chris
Abstract: Background: Shoulder pain is a common musculoskeletal problem. Despite this, much uncertainty still exists regarding diagnosis, prognosis and effectiveness of treatments. One diagnostic challenge is determining the role of the neck when a patient complains of shoulder pain. The aim of this survey was to investigate healthcare professionals' indications for examining the neck in this case and subsequent methods used. Methods: An online survey was developed and distributed via Twitter and the authors' professional networks. Responses were collected over a 4‐week period in 2019. Results: In total, 918 respondents replied; 804 completed the full survey. The majority were physiotherapists. Over 80% would examine the neck of patients presenting with shoulder pain. The most commonly used method was neck active range‐of‐movement testing ( n = 822/95.3%), followed by neurological examination ( n = 713/78.1%). Less commonly used tests were neck resistance testing, palpation of the neck and Spurling's test. Fewer numbers ( n = 176/22%) resorted to using diagnostic tests such as imaging. Conclusions: This survey provides some insight as to how healthcare practitioners examine the neck when a patient complains of shoulder pain. Most would examine based on anterolateral shoulder pain, using variable combinations of movement, resistance, neurological and palpation/other testing. A minority would perform diagnostics or imaging. The results of the survey highlight that practice in this area is mixed, which may be due to uncertainty regarding optimal methods. This highlights the need for further work to understand this clinical dilemma better.